Effects of temperature and time of incubation on the formation of histamine in bonito tuna flesh - Sukkon, Piyaporn; Nalinanon, Sitthipong; Yaiyen, Surachai; Areekul, Varipat (Food and Applied Bioscience Journal, 2017)
Nowadays, tuna related food products are usually faced to the problem of histamine contamination. Histamine causes foodborn illness and allergy due to the activities of Morganella morganii and Enterobacter aerogenes. This study tried to simulate the worse case of damaged tuna on effects of temperature and time of incubation on the formation of histamine in bonito tuna flesh. Tuna flesh samples were collected by cutting from bonito tuna and used in experiment. The result showed that microbiological contents of frozen and thawed tuna were below 1.9 x 103 CFU/g. Incubation of tuna flesh at 4°C for 6 h could control histamine content to 27 ppm, in which lower than USFDA regulation (50 ppm). In addition, histamine content in tuna flesh incubated at 25°C for 24 h was found to be 415.5 ppm, which was lower than the hazard level of USFDA regulation at 500 ppm. Inoculation of E. aerogenes in tuna flesh accelerated the formation of histamine to over hazard level within 18 h. Therefore, the information gained from this study can be applied to the process planning of tuna processing and the production of tuna related products.